Are Adults in Poor Health More Likely to Enroll in Public Insurance? - Susan H. Busch; Elizabeth Richardson Vigdor (SAGE Publishing, 2008)
Policies to reduce the number of uninsured people are rarely judged by whether they will increase insurance coverage rates among the chronically ill, despite evidence suggesting that the health benefits of coverage are greatest for these individuals. This paper examines the effect of public coverage expansions on insurance take-up and unmet need by low-income mothers in poor health. We find a 14.3-percentage-point reduction in unmet need among mothers reporting fair or poor health status. Our results suggest that some of this reduction is due to individuals moving from inadequate private coverage to public coverage.